Расчет термического сопротивления загрязнений по стороне охлаждающей воды в пластинчатых теплообменниках промышленных предприятий - Арсеньева, Ольга Петровна (НТУ "ХПИ", 2011)
The processes of fouling formation for cooling water side in plate heat exchangers are investigated. The different types of fouling formation mechanisms are discussed. The influence of process parameters in plate heat exchangers’ channels with complex geometry on the fouling level is analyzed. The mathematical model is proposed for fouling thermal resistance prediction for precipitation and particulate fouling under the different stream velocities
Keywords: пластинчатые теплообменные аппараты; температура охлаждающей воды; механизмы образования отложений; химические реакции; коэффициент пропорциональности